Historical Variations in the Impact of Union Density on Strike Frequency: Some U.K. Evidence - Cameron, Samuel (Relations industrielles / Industrial Relations, 1985)
Considerable debate exists on the influence of fluctuations in unionmembership on strike frequency. On a theoretical level it is possible to advance a number of arguments about the sign and meaning of the regression coefficient on union membership in a strike function (see Kaufman (1982)) so the issue remains primarily an empirical one. This paper attempts to shed some new light on the empirical issue using U.K. evidence.